An Investigation of Stackelberg Mixed Oligopoly with Advertising Competition. (7th May 2017) - Pi, Jiancai; Zhang, Pengqing; Chen, Xuyang
Abstract : This paper conducts a comprehensive investigation of Stackelberg mixed oligopoly with advertising competition. We focus our attention on misleading advertising, and at the same time derive some results that are closely related to profit‐raising entry. Different from Matsumura and Sunada ( Economics Letters, Vol. 119 (2013), pp. 183–185), we find that it is the leadership of the public firm in the advertising stage that may lead to the negative advertising level of the public firm and make the profit of each private firm decrease in the number of the private firms. In addition, we also find that the public leadership in the advertising stage may lead to the negative aggregate advertising level.